HUBUNGAN ANTARA DIAMETER POHON DAN PRODUKSI GETAH DALAM PENYADAPAN GETAH AGATHIS spp - Ishak Sumantri (Jurnal Penelitian Hasil Hutan, 1991)
This paper presents  the resull an invaligation of the relationship between tree diameter and copal production in the Agathis spp tapping. Copal lappings were done using slanted and horizontal tapping patterns on the Agathis trees having diameter between 24 and 40 cm with the age of 20 years.The  results  of data analysis are as follows  :1. At the even  age  Agathis  trees, there was no relationship  between tree diameter and copal production.2.Viewing from the  coefficient of determination,  the contribution of slanted tapping pallern was 12% and horizontal tapping pattern  was  1%. Other  factors  that may affect  copal production are the color of bark and leaf,  crown size and the direction of resin canal.3.Better  relationship between diameter and copal production may  be obtained if the size   of  tapping quare  is proportional  to tree diameter/perimeter.4.Further investigation, by including other variables, is suggested in order to formulatete better relationship.